The Effects of Peer Pressure on Academic Performance of Grade 12 ABM Students in BCP SY 2018–2019 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Peer pressure (social pressure) is the direct influence on people by peers, or the effect on an individual who gets encourage to follow their peers by changing their attitudes, values or behaviors to conform to those of the influencing group or individual. This can result in either a positive or negative effect. However, a person does not need to be a member nor seeking membership of a group to be affected by peer pressure. Peer pressure can decrease one's confidence. It can affect the lives of the students drastically. Peer pressure has moved from strictly face-to-face interaction to digital interaction as well. Social media offers opportunities for adolescents and adults alike to instill and/or experience pressure every day. Research suggests that not just individuals but also organizations, such as large corporations, are susceptible to peer pressures, such as pressures from other firms in their industry or headquarters city. To achieve the goals of this research study, several instruments was utilized in gathering needed information. The researchers prepare the drafts of the questionnaire through the guidance of their adviser. This study used descriptive method of research for the investigation in determining the information. Out of 50 respondents it was found out that females have lower self-esteem than male adolescent. Woods (2004) stated that male to male peer pressure and female putting pressure on both males and females cause male adolescents to be exposed to more peer pressure. Oral pressure, as a way of indirect peer pressure, is used more by male adolescents (Stockdale at al. 2002; Nabuzoka, 2003) According to adolescents’ self-esteem degree score in terms of their socioeconomic level; adolescents with high level of income have a higher degree of self-esteem than middle-income and low-income adolescents. In the light of this information, one can consider that socioeconomic advantages provided by parents to give adolescents a sense of security. According to the research paper called "How Does Peer Pressure Affect Educational Investments?" Authors Leonardo Bursztyn and Robert Jensen took two groups of 11th graders and offered them free SAT prep courses. One group had to sign up publicly, in full view of peers, and the other group signed up confidentially. The experiment was conducted in both honors and non-honors classes. It concluded, peer pressure appears to be a powerful force affecting academic performance of the students.
Keywords: peers, ABM